The case for partnering doctoral students with librarians: a synthesis of the literatures - Harris, Colleen S (Library review (Glasgow), 2011)
Purpose - The purpose of this paper is to ask how the academic library may better position itself to assist with the demonstrated need for improved research ability in doctoral students. The paper examines the literature on doctoral student retention, which demonstrates problems with research self-efficacy in students, and connects this issue to the library literature demonstrating the impact of library instruction.Design methodology approach - The main approach is the review of the literatures in library science on the impact of instruction, and in the wider education literature on student retention and doctoral student attrition.Findings - It was found that library instruction does demonstrably improve student research skills, and that doctoral students are generally underprepared to conduct dissertation level research. There is a case for partnering doctoral students with academic librarians to improve dissertation completion rates and lower attrition due to lack of research skill.Practical implications - The paper demonstrates an obvious need for focus of library instruction on graduate students, and doctoral students in particular. The paper poses a number of research agendas that can be taken up by practitioners in the field, including various models for implementing instruction for doctoral students.Social implications - Attrition from doctoral programs has a burdensome impact on academic institutions, and has been demonstrated to have adverse social, psychological and financial impacts on the doctoral students themselves. The ability of library intervention to alleviate the problem has wide-ranging implications.Originality value - The paper brings a wider literature base to bear on the practice of library instruction, and raises important questions relevant to librarians and graduate faculty about the value of the library to more advanced research students and the current focus of most library instruction programs at the undergraduate levels.